Comorbid Premenstrual Dysphoric Disorder and Bipolar Disorder: A Review - Slyepchenko, Anastasiya; Minuzzi, Luciano; Frey, Benicio N. (Frontiers in Psychiatry, 2021)
Bipolar disorder (BD) differs in its clinical presentation in females compared to males. A number of clinical characteristics have been associated with BD in females: more rapid cycling and mixed features; higher number of depressive episodes; and a higher prevalence of BD type II. There is a strong link between BD and risk for postpartum mood episodes, and a substantial percentage of females with BD experience premenstrual mood worsening of varying degrees of severity. Females with premenstrual dysphoric disorder (PMDD) – the most severe form of premenstrual disturbances – comorbid with BD appear to have a more complex course of illness, including increased psychiatric comorbidities, earlier onset of BD, and greater number of mood episodes. Importantly, there may be a link between puberty and the onset of BD in females with comorbid PMDD and BD, marked by a shortened gap between the onset of BD and menarche. In terms of neurobiology, comorbid BD and PMDD may have unique structural and functional neural correlates. Treatment of BD comorbid with PMDD poses challenges, as the first line treatment of PMDD in the general population is selective serotonin reuptake inhibitors, which produce risk of treatment-emergent manic symptoms. Here, we review current literature concerning the clinical presentation, illness burden, and unique neurobiology of BD comorbid with PMDD. We additionally discuss obstacles faced in symptom tracking, and management of these comorbid disorders.